Radiation Recall Phenomenon: A Literature Review - Charity Kotambunan; Soehartati A. Gondhowiardjo (Radioterapi & Onkologi Indonesia, 2021)
The radiation recall phenomenon is an inflammatory reaction on a previously irradiated area of the body that occurs due to exposure to triggering agents. In cancer settings, radiotherapy is often followed by chemotherapy or other systemic therapies, and this combination can trigger the radiation recall phenomenon. The triggering agents associated with this reaction are generally cytotoxic (e.g., chemotherapy); however, other agents usage has been widely reported. This reaction manifested in various areas of the body, with the skin being the most predilection site. There is no absolute range of radiation doses associated with this reaction. The interaction among radiotherapy components, triggering agents, and time of the agent’s initiation influences the risk and onset of this phenomenon. Although known for a long time, the mechanism is ambiguous. A series of hypothetical theories are described, including their relation to stem cell function and sensitivity, vascular damage, and drug hypersensitivity reactions. Management of this reaction may include modifying triggering agents, administration of steroids, and other symptomatic therapies. In severe cases, surgical intervention can be performed. Comprehensive observational or even experimental databases are needed for this phenomenon to be entirely understood.